Tent Space Approach of Morrey Spaces and Their Application to Duality and Complex Interpolation - Takahiro Ono (Journal of Function Spaces)
The aim in this paper is to establish a new duality property of Morrey spaces and to discover the complex interpolation space between Morrey spaces and Lebesgue spaces. For that purpose, a new space Np,qsRn is introduced by using methods of tent spaces. The space generalizes Morrey spaces and Lebesgue spaces. Furthermore, this scale of spaces is amenable to the complex interpolation space.